2022
DOI: 10.18174/sesmo.18148
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the micro-level dynamics of water reuse adoption by farmers and the impacts on local water resources using an agent-based model

Abstract: Agricultural water reuse is gaining momentum to address freshwater scarcity worldwide. The main objective of this paper was to investigate the micro-level dynamics of water reuse adoption by farmers at the watershed scale. An agent-based model was developed to simulate agricultural water consumption and socio-hydrological dynamics. Using a case study in California, the developed model was tested, and the results showed that agricultural water reuse adoption by farmers is a gradual and time-consuming process. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The results showed that social changes can accelerate farmers' non-cooperative behavior. Shoushtarian et al [28] developed an ABM model to simulate agricultural water use and socio-hydrological dynamics of California. The results showed that ABM helps to evaluate current water reuse management practices in terms of sustainability of water resources.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that social changes can accelerate farmers' non-cooperative behavior. Shoushtarian et al [28] developed an ABM model to simulate agricultural water use and socio-hydrological dynamics of California. The results showed that ABM helps to evaluate current water reuse management practices in terms of sustainability of water resources.…”
Section: Introductionmentioning
confidence: 99%